Evaluation of Feeding Different Digestible Lysine Intake Levels on Semen Characteristics and Body Weight of Broiler Breeders During Pre-Peak and Peak Production - Obi, C.N.; Parker, H.M.; Corzo, A.; McDaniel , C.D. (International Journal of Poultry Science, 2013)
Because research revealing the impact of Lys on reproduction in Broiler Breeders (BB) is sparse, this study was conducted to evaluate the impact of digestible Lys (dLys) on BB semen characteristics and BW. Eighty males were caged individually from 20 to 39 wk of age. Treatment 1 and 2 diets had the same level of dLys (1,000 mg/rooster/day) in a corn-soybean meal based diet (Soy 1000) and distillers dried grains with solubles (DDGS; DDGS 1000) diet, respectively. Treatment 3, 4 and 5 diets had the inclusion of DDGS in order to titrate dLys intake levels of 850 (DDGS850), 700 (DDGS700) and 550 (DDGS550) mg/rooster/day, respectively. Body weight and semen samples were determined every 2 wk from 26 to 38 wk of age. Immediately after semen collection, samples were analyzed for semen volume, sperm viability, sperm concentration and the Sperm Quality Index (SQI). BW of roosters fed Soy 1,000 was higher than the other treatments from wk 26 through wk 38. This excess weight could be due to over estimating the energy content of DDGS resulting in diets that were not isocaloric. At 28 wk and continuing through wk 38, the percentage of dead sperm was highest in roosters fed Soy 1000. Also, at wk 38 plasma testosterone concentrations were higher for roosters fed Soy 1000. In conclusion, varying levels of dLys (1,000-550 mg/rooster/day) in a DDGS based diet does not appear to cause adverse effects on BB male semen quality during pre-peak and peak production.